1998
DOI: 10.1507/endocrj.45.suppl_s27
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone-Induced Tyrosine Phosphorylation of EGF Receptor as an Essential Element Leading to MAP Kinase Activation and Gene Expression

Abstract: Abstract. GH binding to its receptor, which belongs to the cytokine receptor superfamily, activates Janus kinase (JAK) 2 tyrosine kinase, thereby activating a number of intracellular key proteins such as STAT (signal transducers and activators of transcription) proteins and mitogen-activated protein (MAP) kinases, which finally lead to GH's biological actions including gene expression. In contrast to receptor tyrosine kinases, the signalling pathways leading to MAP kinase activation by GH are poorly understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 26 publications
2
45
0
Order By: Relevance
“…It is increasingly appreciated that interactions and crosstalk among signaling pathways allow both integration and diversity in responses to cellular stimuli. EGFR and cytokine receptor family member signaling pathways can interrelate in various ways (Johnson et al, 1996;Fenton and Sheffield, 1997;Wiepz et al, 1997;Yamauchi et al, 1997Yamauchi et al, , 1998Yamauchi et al, , 2000Qiu et al, 1998;Quijano and Sheffield, 1998;Kim et al, 1999;Maus et al, 1999;Badache and Hynes, 2001;Huang et al, 2003;Eisenberg et al, 2004). We previously focused on interactions between GH/GHR signaling and signaling mediated by intrinsic tyrosine kinase growth factor receptors, including EGFR and ErbB-2, in murine preadipocytes (Kim et al, 1999;Huang et al, 2003Huang et al, , 2004a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is increasingly appreciated that interactions and crosstalk among signaling pathways allow both integration and diversity in responses to cellular stimuli. EGFR and cytokine receptor family member signaling pathways can interrelate in various ways (Johnson et al, 1996;Fenton and Sheffield, 1997;Wiepz et al, 1997;Yamauchi et al, 1997Yamauchi et al, , 1998Yamauchi et al, , 2000Qiu et al, 1998;Quijano and Sheffield, 1998;Kim et al, 1999;Maus et al, 1999;Badache and Hynes, 2001;Huang et al, 2003;Eisenberg et al, 2004). We previously focused on interactions between GH/GHR signaling and signaling mediated by intrinsic tyrosine kinase growth factor receptors, including EGFR and ErbB-2, in murine preadipocytes (Kim et al, 1999;Huang et al, 2003Huang et al, , 2004a.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that PRL, growth hormone (GH) and other cytokines may use multiple mechanisms to crosstalk with EGFR and/or ErbB-2 (Johnson et al, 1996;Fenton and Sheffield, 1997;Wiepz et al, 1997;Yamauchi et al, 1997Yamauchi et al, , 1998Yamauchi et al, , 2000Qiu et al, 1998;Quijano and Sheffield, 1998;Kim et al, 1999;Maus et al, 1999;Badache and Hynes, 2001;Huang et al, 2003). For example, GH causes EGFR tyrosine phosphorylation without the activation of EGFR kinase activity (Yamauchi et al, 1997;Kim et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the ErbB-receptors can also be phosphorylated by GH and PRL, a protein related to GH (Yamauchi et al, 1997(Yamauchi et al, , 1998(Yamauchi et al, , 2000. GH was first described to induce Tyr1068 phosphorylation at EGFR in vitro and in vivo (Yamauchi et al, 1997, exogenous GH administration this expression deficit can be reversed (Jansson et al, 1988;Johansson et al, 1989).…”
Section: Growth Hormone Modulation Of Epidermal Growth Factor Signallingmentioning
confidence: 96%
“…ErbB-receptors are not only activated by specific ligands, they can also be activated indirectly by Growth hormone (GH) or Prolactin (PRL) and other growth factors through the JAK-2/STAT pathway (Yamauchi et al 1997(Yamauchi et al , 1998(Yamauchi et al , 2000. EGFR can also be phosphorylated at sites in the intracellular domain as serine and threonine residues (Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The GRB2 adaptor protein binds activated EGFR at phospho-Tyr1068 (Rojas et al, 1996). Interestingly, Yamauchi et al,(1998) demonstrated that binding of growth hormone to its receptor, which belongs to the cytokine receptor superfamily, activates Janus kinase tyrosine kinase, STAT proteins and MAPK that regulate expression of c-fos. This activation depends on phosphorylation of Tyr1068 by Janus kinase tyrosine kinase 2, providing docking sites for Grb2 and Shc protein adaptor and activating MAPK and gene expression.…”
Section: Mechanisms Of Egfr Transactivation By Kinin B1 Receptormentioning
confidence: 99%